Peranan Asam Salisilat pada Interaksi Inang-Patogen Penyakit Kudis Ubijalar (Elsinoe batatas) - Eko Agus Martanto; Christanti Sumardiyono; Haryono Semangun; Bambang Hadisutrisno (Jurnal Perlindungan Tanaman Indonesia, 2003)
The role of salicylic acid on host-pathogen interactions of sweet potato scab disease (E. batatas) was done by measuring (1) the level of resistance of sweet potato cultivars to scab disease, (2) salicylic acid content in sweet potato leaves before inoculation, 3 days, 6 days, and 9 days after inoculation, and (3) effect of salicylic acid to the germination of E. batatas conidia. The result showed that there were different responses of sweet potato cultivars to pathogens infection. Inoculation with E. batatas isolate from Wonosobo (WO2) showed resistant reaction on Muaratakus, moderate resistant on Cangkuang, moderate susceptible on Malothok, and susceptible on Mlg 12549. Resistant cultivar (Muaratakus) has higher salicylic acid content than moderate resistant (Cangkuang), moderate susceptible (Malothok), and susceptible cultivar (Mlg 12549). Salicylic acid inhibited germination of E. batatas conidia.